2023
DOI: 10.1186/s13062-023-00431-4
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-B: an “unknown” protein of the Bcl-2 family

N. V. Pervushin,
G. S. Kopeina,
B. Zhivotovsky

Abstract: Bcl-B is a poorly understood protein of the Bcl-2 family that is highly expressed in many healthy tissues and tumor types. Bcl-B is considered an antiapoptotic protein, but many reports have revealed its contradictory roles in different cancer types. In this mini-review, we elucidate the functions of Bcl-B in normal conditions and various pathologies, its regulation of programmed cell death, its oncogene/oncosuppressor activity in tumorigenesis, its impact on drug-acquired resistance, and possible approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…It is known that the TNFR1 receptor induces alternative processes of the program of the cell’s death: apoptosis and necroptosis [ 30 , 31 , 32 ]. Previously, we showed that necroptosis induced by the Tag7-Hsp70 complex is carried out with the participation of lysosomes and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the TNFR1 receptor induces alternative processes of the program of the cell’s death: apoptosis and necroptosis [ 30 , 31 , 32 ]. Previously, we showed that necroptosis induced by the Tag7-Hsp70 complex is carried out with the participation of lysosomes and mitochondria.…”
Section: Discussionmentioning
confidence: 99%